Penerapan Sistem Informasi Kearsipan Digital untuk Pemerintah Desa - Ryan Hamonangan; Saeful anwar; Ibnu Hajar; Ike Suryani Dewi (CV. Multi Kreasi Media, 2022)
In the digital era, an archival information system is an important requirement in supporting effective and efficient administrative governance in the village government. Many villages in Indonesia still use a manual archive recording system that is vulnerable to data loss, physical damage to documents, and the slow process of retrieving information. This service program aims to implement a digital-based archival information system in the village government to improve administrative performance and public services. The methods used include partner needs analysis, system design, software implementation, user training, and evaluation of results. The developed system enables document digitization, archive grouping, and fast data search, and is equipped with security features to maintain information integrity. The results of the implementation showed that village officials were able to understand and operate the system well after the training. The information system significantly speeds up the document search process and reduces the risk of data loss. In addition, the implementation of the system also has an impact on improving transparency, accountability and professionalism in services to the community. In conclusion, the implementation of a digital-based archival information system is an innovative and applicable solution to address the challenges of modern village archive management.